Measuring Lower Uterine Segment Thickness Using Abdominal Ultrasound to Predict Timing of Cesarean Section in Women with Scarred Uterus at Elwiya Maternity Teaching Hospital - Sarsam, Samar Dawood; Kadem, Heba Abul (AL-Kindy College Medical Journal, 2013)
Background: Ultrasonography has been used to examine the thickness of the lower uterine segment in women with previous cesarean sections in an attempt to predict the risk of scar dehiscence during subsequent pregnancy. The predictive value of such measurement has not been adequately assessed. Objectives: To correlate lower uterine segment thickness measured by trans abdominal ultrasound in pregnant women with previous cesarean section with that measured during cesarean section by caliper and to find out minimum lower uterine segment thickness indicative of integrity of the scar.Methods: A prospective observational study at Elwyia Maternity Teaching Hospital, from January 2011 to January 2012. A total of 143 women were enrolled in the study. Those women who were included were pregnant with gestational age (36-40) weeks, all had history of previous one or more cesarean section. Transabdominal ultrasound measurement of thickness uterine segment thickness done with moderately full bladder before delivery and correlated with these measured directly during operation using a caliper. The sensitivity and specificity of ultrasound calculated with positive and negative predictive value. Results: The sensitivity and specificity of trans abdominal ultrasound in detecting patient at risk of scar dehiscence in patient with previous and cesarean section not starting uterine contractions were very high 90%and 92% respectively with positive and negative predictive value of 90% and 92% respectively with a cut off value of uterine segment thickness of 4.5 mm. It was also has high sensitivity and positive predictive value of 93.4% and 93% respectively with patients that started labor but with low specificity and negative predictive value of 50% and 38% respectively with the same cut off value.Conclusions: Sonographic lower uterine segment thickness is a strong predictor for uterine scar defect in women with prior Caesarean section. However, no ideal cut-off value can yet be recommended, whenever uterine contractions started. But this method carries a high sensitivity and specificity in patients who did not start uterine contractions with a cut-off value of 4.5 mm.